Pendampingan Manajemen Waktu Berbasis Digital dalam Menyeimbangkan Aktivitas Akademik dan Ekstrakurikuler Siswa SMP di Pondok Pesantren Al Kaffah - Kamilah, Hilda Sa’idatul; Susanti, Astri Ardila; Rittiauw, Mutiara Vidrin; Nurazizah, Zizah; Ilwandi; Dermawan, Afrinal Desi (CV. Kurnia Grup, 2026)
This community service program was motivated by the low level of students’ time management skills in balancing academic and extracurricular activities, particularly in Islamic boarding school environments characterized by structured schedules and limited access to digital technology. The focus of this program was digital-based time management assistance adapted to the contextual conditions of the pesantren. The objective of this activity was to improve students’ understanding and skills in managing time effectively and systematically. The method employed a participatory approach with educational and contextual strategies, including lectures, discussions, reflections, manual simulations, and demonstrations. The program was implemented through three main stages: preparation, implementation, and evaluation, with data collected through observation, interviews, and documentation, and analyzed using a descriptive qualitative approach. The results indicate that students experienced an improvement in their understanding of time management concepts, demonstrated the ability to create more structured daily schedules, and developed greater awareness in setting activity priorities. In addition, students gained conceptual knowledge of how digital tools can support time management, despite not directly using digital devices. Therefore, this program contributes to fostering students’ self-regulated learning, discipline, and ability to balance academic and extracurricular activities in the pesantren environment.